Argumentation Through the Concept of Qadar as Depicted in Qurân - Fouly, Nabil (DINIKA : Academic Journal of Islamic Studies, 2019)
This paper revolves around those verses of Quran in which Quran states the argument of the non-believers provide for the justification of their disbelief and acts of polytheism and that is the argument of Qadar. The argument follows that the non-believers are not to be blamed for their disbelieve because these acts are been decreed by God for them. The paper emphasises upon a detail analysis of their argument and upon the quranic response to them by exposing their flawed argumentation and wrong claim. The paper then studies and establishes the position of belief in qadar and it’s position and place within the Islamic belief system, and furthermore studies those different issues which are discussed and dealt within those Quranic verses related to qadar. Moreover the interpretations of those Quranic verses which states this claim of non- believers according to different Mufassirin are studied and analysed and then in the end a general Quranic view regarding how Quran deals with the issue of “ärgumentation based upon the concept of Qadar” is presented in the paper.